Efeitos das isoflavonas na função sexual na pós-menopausa - Araujo, Teresa Raquel Embirucu de [UNIFESP] (2013)
Objective: The purpose of this study was to analyze the effects of soybean extract with high concentration of isoflavones in postmenopausal sexual function by the sexual questionnaire Female Sexual Function (FSFI) and vaginal cytology. Materials and methods: This is a randomized, double-bind, placebocontrolled clinical trial with 84 postmenopausal patients. The patients were allocated in two groups: Group A, with 43 patients receiving 60mg daily of oral isoflavones, and Group B, with 41 receiving placebo. The power calculation of 80% was 90 patients. Results: There was not difference between both groups in relation to FSFI domains: sexual desire, arousal, lubrication, satisfaction and pain (p>0.05). The maturation value of vaginal epithelium of group A was similar to group B. Conclusion: Our data suggests the isoflavones may not have benefits on the postmenopausal sexual function.